Analisis Daya Tampung Waduk Sebagai Pengendali Banjir di Kawasan Sungai Wanggu - Eva Safitri Maladeni; Nelam Patricia (Universitas Batanghari Jambi, 2023)
Reservoir Boulevard is part of the flood control system in the city of Kendari, like other areas in Indonesia. Wanggu Reservoir is located in Lepo Lepo Village, Baruga District, Kendari City. The reservoir has a storage volume of 267.142m3. danluas DAS wanggu 348,75 km2. This flood control reservoir functions to accommodate flood overflow from the Wanggu River when it rains with high intensity. So in this study to determine the capacity of the reservoir capacity from year to year, a design rain analysis was carried out with return periods of 2, 5, 10, 25, 50, 100 years. It is necessary to analyze the design rainfall to find out whether the reservoir can reduce flooding for up to 100 years or not. In the rain analysis this plan uses the log person type III method and the flood discharge analysis uses the Rational Method. From the research results, it was found that the flood discharge with a return period of 100 years is 9,670m3/the.